Clinical impact of pharmacogenomics in pediatric care: insights extracted from clinical exome sequencing - Maggo, Simran; Pan, Yachen; Ostrow, Dejerianne; Nguyen, Jenny Q.; Biegel, Jaclyn A.; Deardorff, Matthew A.; Gai, Xiaowu (Frontiers in Genetics, 2025)
IntroductionPharmacogenomic (PGx) testing improves drug efficacy and reduces risk of toxicity for commonly prescribed medications, with most pharmacogenomic studies largely focused on individuals of European descent to date. The impact of pharmacogenomic testing in a racially diverse population is still emerging, especially for Admixed American patients.MethodsIn this study, we assessed the frequency of actionable PGx variants by analyzing anonymized exome sequencing data of a racially diverse cohort of 1777 pediatric patients, collected for routine clinical genetic diagnosis at Children‘s Hospital Los Angeles (CHLA). Utilizing exome data, we used the Illumina DRAGEN germline pipeline v4.2, to determine the predicted phenotypes of 25 pharmacogenes including HLA‐A and HLA‐B, including CPIC Level A genes and genes recommended for PGx testing by the U.S. Food and Drug Administration. To assess cross-platform consistency, we compared our results to those generated by PyPGx, a pharmacogenomic genotyping tool developed by the same author as Stargazer. As the distribution of PGx alleles is ancestry specific, we estimated genetic ancestry bioinformatically using the Somalier tool.ResultsGenetic ancestry analysis demonstrated that 62% of our cohort was Admixed American, followed by 23% European, 8% East Asian, 5% African American, and 2% South East Asian. Actionability analysis showed that: 1) 93% of all exome cases had at least one actionable PGx phenotype, 2) one in five cases (22%) had at least three actionable PGx phenotypes, and 3) CYP2B6 (54%) and CYP2D6 (33%) had the highest number of actionable phenotypes. Further analysis revealed notable differences, including higher rates of poor metabolizers for CYP2B6 and variations in CYP2D6 metabolizer statuses, in PGx phenotypes compared to previously collated frequencies in the PharmGKB database, especially within the Admixed American population.DiscussionIn conclusion, our study reinforces the importance of PGx testing, underscores the diversity of PGx variation in ancestral backgrounds, and supports the clinical utility of preemptive PGx testing using exome or genome sequencing approaches.